HARMONIZATION OF INTELLECTUAL AND EMOTIONAL IN IMPROVING LESSON EFFICIENCY IN THE MODERN SCHOOL - N.Ye. Fedorinova (Academy of Cognitive and Natural Sciences, 2008)
The article deals with possibilities of interaction of intellectual and motional factors of the modern lesson in providing quality education for students.